Creativity and health in personality’s being [Креативность и здоровье в экзистенции личности] (in Russian) - Иванченко, Андреянна Алексеевна; Ivanchenko, Andreyanna; Іванченко, Андреянна Олексіївна (Х.: ХНУ імені В.Н. Каразіна, 2013)
The current social situation, the development of science and the spiritual-value orientations of public opinion are in many respects similar to the scientific and social trends at the end of the second half of the 20th century, in which the orientation towards a person with creative potential, developed cognitive activity and a formed focus on self-realization became socially demanded. Современная социальная ситуация, развитие науки и духовно-ценностных ориентаций общественного мнения во многом аналогичны научной и общественной тенденции конца второй половины XX века, при которой социально востребованной становилась ориентация на личность, имеющую творческий потенциал, развитую познавательную активность и сформированную нацеленность на самореализацию.
Иванченко А.А., доцент, канд. психол. наук Харьковский национальный университет имени В.Н.°Каразина, г. Харьков, Украина.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology; креативность; здоровье в экзистенции личности; валеологія